Taking action on climate change: testimonials and position statement from the international league against epilepsy climate change commission - GÜLÇEBİ İDRİZ OĞLU, MEDİNE (My University, 2023)
The release of the 2021 Intergovernmental Panel on Climate Change (IPCC) report makes clear that human activities have resulted in significant alterations in global climate. There is no doubt that climate change is upon us; chronic global warming has been punctuated by more frequent extreme weather events. Humanity will have to mitigate climate change and adapt to these changing conditions or face dire consequences. One under-appreciated aspect of this global crisis is its impact on healthcare, particularly people with epilepsy and temperature-sensitive seizures. As members of the inaugural International League Against Epilepsy (ILAE) Climate Change Commission, we recount the personal motivations that have led each team member to decide to take action, in the hope that our journeys as ordinary clinicians and scientists will help persuade others that they too can act to foster change within their spheres of influence.
Keywords: Tıp; Dahili Tıp Bilimleri; Nöroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Neurology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; KLİNİK NÖROLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; CLINICAL NEUROLOGY; Yaşam Bilimleri; Nöroloji (klinik); Life Sciences; Neurology (clinical); Epilepsy; Global crisis; Global warming; Seizure